PRIMARY OVARIAN BURKITTS LYMPHOMA - Jan, Zainab; Khan, Aakif Ullah; Ilyas, Abbas; Faiz, Sidra (Journal of Ayub Medical College Abbottabad, 2024)
Primary ovarian Burkitt lymphoma (BL) is a very rare and aggressive malignancy. We report an 18-year-old female patient who presented with a large, tender abdomen, and highly de-ranged renal and liver functions. Ultrasonography showed hepatosplenomegaly, mild ascites, dilated biliary channels and a heterogeneous pelvic mass of size 15´10´6.4 cm. Immunohistochemical (IHC) staining of the biopsy sample excised from the left ovary demonstrated reactivity for CD20 and CD10, and negativity for CD3, Bcl-2 and TdT. The C-myc translocation was positive in 60% of tumour cells. Moreover, the proliferation index was 90%. These features were consistent with BL. After haemodialysis, the patient was planned for multiagent chemotherapy, including cyclophosphamide, doxorubicin, vincristine and prednisone. This case supports the hypothesis that primary ovarian BL is an aggressive malignancy that appears to respond promisingly to multi-agent chemotherapy.